Neostigmine induced postoperative airway edema: a case report (Indian Journal of Case Reports, 2016)
A 12 year old patient was taken up for adenotonsillectomy. Preoperative and intraoperative course was normal. Reversal of neuromuscular blockade was done with injection Neostigmine and extubation was done after a thorough oropharyngeal examination by the surgeon and anaesthesiologist. Within minutes the patient developed stridor with a fall in oxygen saturation to 77% on room air. Laryngoscopy revealed a gross uvular and posterior pharyngeal wall edema. Patient was immediately intubated and injection Adrenaline, Dexamethasone and Chlorpheniramine maleate were administered. Postoperative serum tryptase and Immunoglobulin E levels were raised. Elective ventilation was done overnight and patient was extubated next day after confirming a reduction in the oropharyngeal edema. Skin prick tests were done two months postoperatively which showed a positive reaction to neostigmine. The test was negative for other drugs used in the intraoperative period.